(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
During this search all rings are commutative and all modules are unitary. In this search we introduced the concept of Restrict Nearly semi-prime Sub-modules as generalization of semi-prime Sub-modules and give some basic properties, examples and charactarizations of this concepts and stablished some sufficient conditions on Restrict Nearly semi-prime to be semi-prime